2014
DOI: 10.1128/jcm.01819-14
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Diagnosis and Treatment Follow-Up of Human Brucellosis by a Novel Quantitative TaqMan Real-Time PCR Assay: a Human Clinical Survey

Abstract: cRapid and effective diagnosis of brucellosis is a challenge for clinicians. Even when diagnosis is on time and therapy is initiated, meticulous follow-up appointments are crucial for ensuring the efficacy of the treatment. Due to shortcomings of serological methods, molecular diagnosis, especially real-time PCR, is becoming a main approach in laboratory diagnostics. Thus, the development of efficient procedures and standardization of the PCR tests will have a great impact on the precise detection and quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…Thus some proportion of samples that were positive by culture was negative by qPCR (Debeaumont et al, 2005), similarly samples positive by IS711 PCR assay have been shown negative by culture (Sanjuan-Jimenez et al, 2013). Choice of media selected for isolation by culture may also affect sensitivity (Her et al, 2009;Sohrabi et al, 2014;Dean et al, 2014). The range of C q values of clinical samples positive for brucellosis reported in the current study were similar (C q -33.3±4.6) to those reported earlier (Colmenero et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus some proportion of samples that were positive by culture was negative by qPCR (Debeaumont et al, 2005), similarly samples positive by IS711 PCR assay have been shown negative by culture (Sanjuan-Jimenez et al, 2013). Choice of media selected for isolation by culture may also affect sensitivity (Her et al, 2009;Sohrabi et al, 2014;Dean et al, 2014). The range of C q values of clinical samples positive for brucellosis reported in the current study were similar (C q -33.3±4.6) to those reported earlier (Colmenero et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
“…Their studies had indicated that the DSe could vary from 64.7% to 88% and DSp 98.3% to 100%. Previously the estimates of diagnostic qPCR for brucellosis had been calculated based on case-wise (Surucuoglu et al, 2009) and also on sample-wise status in humans and in animals (Debeaumont et al, 2005;Sanjuan-Jimenez et al, 2013;Sohrabi et al, 2014), and on comparison with status by culture (Amoroso et al, 2011;El Behiry et al, 2014), serology (Gwida et al, 2011;Menshawy et al, 2014;Sohrabi et al, 2014) and In the present study, we have optimized and validated the diagnostic estimates of qPCR by animal-wise and sample-wise approach comparing the culture status in the first instance and the combined culture and serology status in the second instance. The multiple approach adopted for derivation of diagnostic estimates led to interesting observations.…”
Section: Discussionmentioning
confidence: 99%
“…The Rose Bengal test has high sensitivity and specificity, but positive results can occur in asymptomatic patients after exposure to Brucella or vaccination 20 . Real-time PCR was considered as the gold-standard method for diagnosis because Brucella can only be cultured in laboratories with at least a biosafety level for three 21,22 . Symptomatic patients (symptoms suggesting brucellosis) with positive a PCR or a reagent EIA IgM should receive treatment, after excluding other potential causes of the symptoms.…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…A resolução do sistema de detecção dos produtos amplificados na PCR em tempo real é considerada maior do que na PCR convencional, já que a primeira é baseada na emissão de fluorescência pelos produtos amplificados que são marcados com corantes intercalantes fluorescentes ou pelo uso de sondas marcadas com fluoróforos, a qual é detectada por um leitor de fluorescência. Já na PCR convencional, a verificação dos produtos amplificados é feita visualmente, pela observação dos produtos amplificados em gel de agarose após a coloração com brometo de etídio, sob luz ultravioleta (DEBEAUMONT; FALCONNET; MAURIN, 2005;KATTAR et a., 2007;BOUNAADJA et al, 2009;SOHRABI et al, 2014;HÄNSEL et al, 2015;KHAMESIPOUR, 2015;KADEN et al, 2017;LINDAHL-RAJALA et al, 2017).…”
Section: Epidemiologiaunclassified
“…Tabela 4-Resultados dos testes de hemocultura, PCR convencional (PCRc) e PCR em tempo real utilizando o protocolo B (PCRtr-B) realizado à temperatura de annealing de 59ºC e utilizando-se 200 nM de primers em oito amostras de DNA obtidas de sangue canino, para a detecção de Brucella spp. BOUNAADJA et al, 2009;SOHRABI et al, 2014;HÄNSEL et al, 2015;KHAMESIPOUR, 2015;KADEN et al, 2017;LINDAHL-RAJALA et al, 2017), no entanto, ao longo deste estudo foi observado que o método apresentou falhas, uma vez que houve amplificação de alguns controles negativos da extração e também amplificação de diversas amostras que tinham sido negativas nos outros testes usados para diagnóstico de infecção por B. canis (hemocultura e PCR convencional).…”
Section: Hemocultura Positivo E Pcrc Positivounclassified